Lack of relationship between hypertension and cognitive performance in community dwelling older adults (Archives of Clinical Psychiatry, 2010)
BACKGROUND: Studies suggest that hypertension might be involved in cognitive decline among older adults. It is estimated that up to 60% of older adults have hypertension, what makes them more vulnerable to cognitive decline. OBJECTIVE: The objective of this study was to investigate the relationship between hypertension and cognitive performance in non-demented non-depressed older adults. METHOD: The sample was constituted by community dwelling older adults from an on-going epidemiological study which includes all senior citizens residing in Amparo (SP). Following inclusion and exclusion criteria, 80 seniors (40 diagnosed as having hypertension), including men and women over 60, were recruited. Both groups were equivalent as to socio-demographic and other health variables. In order to evaluate depressive symptoms the Geriatric Depression Scale (GDS) was used. The cognitive tests included the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) neuropsychological battery, the Clock Drawing Test, and Digit Span Forward and Backward. Logistic regression analyses with univariate and multivariate models and cluster analyses were carried out. RESULTS: No significant differences were found between the two groups. The difference for verbal fluency approached statistical significance (p = 0.075). DISCUSSION: Present results may be explained by the high compliance of the studied sample to the antihypertensive drug regimen. Longitudinal studies will be needed to continue to investigate the relationship between hypertension and cognition in aging.